Examining the Place of History in Peace and Conflict Education – Experience from Peace and Conflict Programme, University of Ibadan - Nigeria - Ekpo, Charles E. (American Journal of Social Sciences and Humanities, 2019)
There is always a romance between the present and the past. Peace and conflict studies, as a discipline is not immune to such covering law as its praxis of context profiling suffices in establishing the dots between an event and its cause and effect connections. Nevertheless, context profiling might be superficial and sui generis to a specific conflict of interest. The observation, therefore, is that students of peace studies often lack sufficient depth in case studies and instances in their specialization, but for autodidacts which in the observed case is a rarity. Consequently, the focus of the work is to justify the need for the introduction of courses that address specific themes of history of conflict with peculiarity to various specializations in peace studies programmes. To the Ibadan Peace and Conflict Programme, we recommend the introduction of courses as (i) historical cases of border-related conflicts (for borderland specialists) (ii) historical cases of environment-related conflicts (for environmental conflict specialists) (iii) historical cases of international conflicts (for international conflict specialists) and (iv) selected themes of conflict in the history of Nigeria (for internal conflict specialists). The descriptive research design was utilized and data was qualitatively collected and presented. Primary data was generated through direct participant observation and secondary data sourced from existing literatures.